Assessment of the Impact of Adhesive and Wires Types on the Tensile Bond Strength of Fixed Lingual Retainers Used in Orthodontics: An In Vitro Study - Ahmed Ibrahim Alhakim; Akram Faisal Alhuwaizi (Wolters Kluwer Medknow Publications, 2023)
Introduction: We aimed to assess the impact of adhesive and wires types on the tensile bond strength of fixed lingual retainers. Methods: A total of 160 intact bovine teeth were collected, cleaned, stored in 25% sodium hypochlorite, and randomly assigned to two groups based on the adhesive type: a two-step adhesive and a one-step adhesive. Each group was further divided into four subgroups based on the type of lingual retainer wire, which included (A) 8-strand braided stainless steel wire, (B) three-strand titanium retainer wire, (C) stainless steel chain, and (D) fiber-reinforced retainer. A tensile bond strength test was conducted using a universal testing machine at a controlled speed of 10 mm/min. Result: The 8-strand braided stainless steel wire and stainless steel chain bonded by one-step self-priming adhesive showed significantly higher tensile bond strength (P < 0.001). The adhesive wire significantly affected the tensile bond strength (P < 0.001). Conclusion: Within the limitations of this in vitro study, it can be concluded that stainless steel wire and chain bonded by one-step self-priming adhesive showed higher tensile bond strength.